Stress evolution during the oxidation of silicon nanowires in the sub-10 nm diameter regime - Kim, Byung-Hyun; Pamungkas, Mauludi Ariesto; Park, Mina; Kim, Gyubong; Lee, Kwang-Ryeol; Chung, Yong-Chae (AMER INST PHYSICS, 2011)
Using a reactive molecular dynamics simulation, the oxidation of Si nanowires (Si-NWs) with diameters of 5, 10, and 20 nm was investigated. The compressive stress at the interface between the oxide and the Si core decreased with increasing curvature in the sub-10 nm regime of the diameter, in contrast to the theory of self-limiting oxidation where rigid mechanical constraint of the Si core was assumed. The Si core of the thinner Si-NW was deformed more with surface oxidation, resulting in a lower compressive stress at the interface. These results explain the experimental observation of full oxidation of very thin Si-NWs. (C) 2011 American Institute of Physics. [doi:10,1063/1.3643038]
Keywords: SELF-LIMITING OXIDATION; SI NANOWIRES; PARTICLES